2012
DOI: 10.1024/1662-9647/a000053
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Quality of Life (fQOL)-Model

Abstract: Quality of life (QOL) is increasingly being suggested as a crucial outcome variable for interventions that aim to maintain or improve health and psychological resources in old age. Currently, two main approaches to measuring QOL can be distinguished: (1) the sQOL approach which measures an individual’s subjective evaluation of his or her overall life situation and QOL; (2) the oQOL approach that infers QOL of an individual from the outside, e.g., via measurement of health impairments. Both approaches, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Finally, the present study’s functional determinants were qualities, skills, and resources, which enabled OAs to optimally adapt to different situations and maintain their QoLs. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the present study’s functional determinants were qualities, skills, and resources, which enabled OAs to optimally adapt to different situations and maintain their QoLs. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…First, it must be noted that even after 80 years of QoL research, there is still no reliable and common definition of this construct (Martin et al, 2012; Veenhoven, 2000). However, there seems to be a basic differentiation between the assessment of objective and subjective QoL: On the one hand QoL evaluations from outside on the basis of objectively measurable circumstances (e.g., assessment of health impairments), and on the other hand intraindividual, and thus subjective, QoL judgments (Martin et al, 2012).…”
Section: Geriatric Rehabilitation and Its Aim To Foster Quality Of Lifementioning
confidence: 99%
“…Yet, major improvements with regard to objective resources are not necessarily connected to major improvements in subjective QoL: It has been found that interventions targeting enhanced engagement in physical activity and improved functional ability have, if any, only rather small effects on well-being (Clark et al, 2012; Martin et al, 2012; Netz, Wu, Becker, & Tenenbaum, 2005). This finding of a relatively weak connection between objective and subjective QoL indicators can also be seen as being in agreement with the insights on the well-being paradox that despite deteriorating health, well-being remains stable or does not deteriorate as much as health parameters over a longer period of time (Staudinger, 2000).…”
Section: The Relation Between Objective and Subjective Quality Of Lif...mentioning
confidence: 99%
“…In doing so, the model offers a new flexibility to address quality of life outcomes beyond the hedonic realm. This includes functional [17] or eudemonic conceptions of quality of life [26] that are likely to be of particular relevance in very old age. The “Functional Quality of Life (fQOL)” model [17] considers the subjective evaluation of the individual’s resources to fulfil meaningful activities and goals.…”
Section: Quality Of Life Of the Very Oldmentioning
confidence: 99%
“…This includes functional [17] or eudemonic conceptions of quality of life [26] that are likely to be of particular relevance in very old age. The “Functional Quality of Life (fQOL)” model [17] considers the subjective evaluation of the individual’s resources to fulfil meaningful activities and goals. In our understanding, the conduct of activity may imply a grossly underestimated outcome quality, even if it does not (instantly) resolve in hedonic (e. g. wellbeing, happiness) quality of life outcomes.…”
Section: Quality Of Life Of the Very Oldmentioning
confidence: 99%